Cisco express forwarding - Stringfield, Nakia (Networking technology series., 2007)
Cisco Express Forwarding Understanding and troubleshooting CEF in Cisco routers and switches Nakia Stringfield, CCIE® No. 13451 Russ White, CCIE No. 2635 Stacia McKee How does a router switch a packet? What is the difference between routing a packet, switching a frame, and packet switching? What is the Cisco® Express Forwarding (CEF) feature referred to in Cisco documentation and commonly found in Cisco IOS® commands? CEF is a general term that describes the mechanism by which Cisco routers and Catalyst® switches packet-switch (route) frames. CEF is found in almost all Cisco routers and Catalyst switches, and understanding how CEF operates can improve the performance, scalability, and efficiency of your network. Cisco Express Forwarding demystifies the internal workings of Cisco routers and switches, making it easier for you to optimize performance and troubleshoot issues that arise in Cisco network environments. This book addresses common misconceptions about CEF and packet switching across various platforms, helping you to improve your troubleshooting skills for CEF- and non-CEF-related problems. The first part of the book provides an overview of packet-switching architectures and CEF operation and advanced features. It also covers the enhanced CEF structure and general troubleshooting. The second part of the book provides case studies that focus on the common topics that have been problematic for customers and those supporting Cisco networks. Full of practical examples and configurations, this book draws on years of experience to help you keep your Cisco networks running efficiently. Nakia Stringfield, CCIE® No. 13451, is a network consulting engineer for Advanced Services at Cisco, supporting top financial customers with network design and applying best practices. She was formerly a senior customer support engineer for the Routing Protocols Technical Assistance Center (TAC) team troubleshooting issues related to CEF and routing protocols. Nakia has been with Cisco for more than six years, previously serving as a technical leader for the Architecture TAC team. Russ White, CCIE No. 2635, is a Principle Engineer in the Routing Protocol Design and Architecture team at Cisco. He is a member of the IETF Routing Area Directorate, co-chair of the Routing Protocols Security Working Group in the IETF, a regular speaker at Cisco Networkers, a member of the CCIE Content Advisory Group, and the coauthor of six other books about routing and routing prot ...